An elementary introduction to the Wolfram language - Wolfram, Stephen, 1959- (Champaign : Wolfram Media, 2015)
The Wolfram Language represents a major advance in programming languages that makes leading-edge computation accessible to everyone. Unique in its approach of building in vast knowledge and automation, the Wolfram Language scales from a single line of easy-to-understand interactive code to million-line production systems. This book provides an elementary introduction to the Wolfram Language and modern computational thinking. It assumes no prior knowledge of programming, and is suitable for both technical and non-technical college and high-school students, as well as anyone with an interest in the latest technology and its practical application.
Includes bibliographical references and index.
Keywords: Wolfram language (Computer program language).; Mathematica (Computer file).